2011
DOI: 10.1186/1471-2091-12-25
|View full text |Cite
|
Sign up to set email alerts
|

The existence of an insulin-stimulated glucose and non-essential but not essential amino acid substrate interaction in diabetic pigs

Abstract: BackgroundThe generation of energy from glucose is impaired in diabetes and can be compensated by other substrates like fatty acids (Randle cycle). Little information is available on amino acids (AA) as alternative energy-source in diabetes. To study the interaction between insulin-stimulated glucose and AA utilization in normal and diabetic subjects, intraportal hyperinsulinaemic euglycaemic euaminoacidaemic clamp studies were performed in normal (n = 8) and streptozotocin (120 mg/kg) induced diabetic (n = 7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Moreover, Koopmans et al. () demonstrated that increased pFAAs in patients with TD were much more easily disposable than glucose, which may partly be responsible for glucose intolerance. Plasma free amino acids increased along with hyperglycaemia herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Koopmans et al. () demonstrated that increased pFAAs in patients with TD were much more easily disposable than glucose, which may partly be responsible for glucose intolerance. Plasma free amino acids increased along with hyperglycaemia herein.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that plasma alanine level (Mochida et al, 2011) was significantly elevated in a TD1 model (ins 2À/À mice) after 2-h fasting. Moreover, Koopmans et al (2011) demonstrated that increased pFAAs in patients with TD were much more easily disposable than glucose, which may partly be responsible for glucose intolerance. Plasma free amino acids increased along with hyperglycaemia herein.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models of spontaneous type 1 diabetes (Non-Obese Diabetic or NOD mice; BioBreeding or BB rats, also called BioBreeding Diabetes Prone BB-DP rats) and experimentally-induced diabetes (e.g., β-cell cytotoxic drugs like alloxan or streptozotocin, or pancreatectomy which is not usually done in rodents) are commonly applied, also in studies on prevention, immunologic mechanisms, and metabolic function (Van Belle et al, 2009). Pigs are primarily used to model type 2 diabetes and the mechanisms underlying dyslipidemia and atherosclerosis (Fricker, 2001;Gerrity et al, 2001), and also the effects of dietary interventions owing to closer similarity to humans in food intake patterns and metabolism (Koopmans et al, 2006(Koopmans et al, , 2011. Pigs with experimentally-induced diabetes are used to model the T1D state, though less frequently (Grüßner et al, 1993;Larsen and Rolin, 2004).…”
Section: Introduction Type 1 Diabetesmentioning
confidence: 99%
“…This study found that the simultaneous dietary administration of fish protein and fish oil, which is achieved by the intake of intact fish muscle, has hypocholesterolemic effects that help prevent hyperlipidemia and atherosclerosis. In another study (Koopmans et al, 2011), the ratio of insulin-stimulated glucose versus amino acid clearance was decreased 5.4-fold in diabetic pigs, which was caused by a 3.6-fold decrease in glucose clearance and a 2.0-fold increase in non-essential amino acid clearance. In parallel with the Randle concept (glucose-fatty acid cycle), the present data suggest the existence of a glucose and non-essential amino acid substrate interaction in diabetic pigs whereby reduced insulin-stimulated glucose clearance seems to be partly compensated by an increase in non-essential amino acid clearance whereas essential amino acids are preferentially spared from an increase in clearance.…”
Section: Essential and Nonessential Amino Acidsmentioning
confidence: 99%
“…Effect of glutamate on brain function: Gustatory and anticipatory cephalic stimuli during a meal yield nutritional information and aid efficient food digestion (Uneyama et al, 2008;McCabe and Rolls, 2007;Young and Ajami, 2000;Tomporowski, 2003;Koopmans, 2011;Uematsu et al, 2009;2010;Kitamura et al, 2011). There is evidence that mammals, including humans, can detect the amount of dietary protein and its quality via cephalic relay to initiate proper digestion in the upper gastrointestinal tract.…”
Section: Effects Of Diet On Risk Of Cardiovascular Diseasementioning
confidence: 99%